Sex differences in cardio-metabolic and cognitive parameters in rats with high-fat diet-induced metabolic dysfunction. Issue 11 (June 2020) - Shin, You Kyoung; Hsieh, Yu Shan; Han, A Young; Kwon, Soonho; Seol, Geun Hee
Excessive dietary fat intake is related to metabolic dysfunction and enhances susceptibility to hypertension and cognitive impairment. Although there are sex differences in the prevalence and progression of these diseases, few studies have investigated sex differences in cardio-metabolic and cognitive parameters in rats with high-fat diet-induced metabolic dysfunction. To better reflect actual clinical conditions, sex-differences in rats with high-fat diet-induced metabolic dysfunction were evaluated. Male and female Sprague-Dawley rats were fed a high-fat diet to induce metabolic dysfunction and intraperitoneally injected with N-nitro-L-arginine methyl ester and scopolamine to model vulnerability to hypertension and cognitive impairment, respectively, whereas control rats were fed a regular diet and treated with distilled water and 0.9% saline. Male experimental rats showed significantly higher systolic blood pressure than female experimental animals. More importantly, acetylcholine-induced relaxation of carotid arteries was decreased only in the male experimental rats, revealing a significant difference compared with female experimental rats. These findings provide evidence for individualized sex-based management of patients with metabolic dysfunction and susceptibilities to hypertension and cognitive impairment. Impact statement: Excessive dietary fat intake plays important roles in the process of metabolic dysfunction and increases susceptibilities to chronic diseases such as hypertension. Few previous studies, however, have accurately reflected real-world medical conditions. In addition, studies performed to date have not examined detailed sex-differences in cardio-metabolic and cognitive parameters, precluding the development of sex-tailored interventions for patients with metabolic dysfunction who are susceptible to hypertension and cognitive impairment. In this study, using rats with HFD-induced metabolic dysfunction that made them susceptible to hypertension and cognitive impairment, we demonstrate that male rats show greater impairment of acetylcholine-induced vasorelaxation of the carotid artery and systolic blood pressure compared to female rats. These findings may provide a basis for the early detection of carotid artery dysfunction and systolic blood pressure increase, especially in males.